Association of Platelet-to-Lymphocyte Ratio and Neutrophil-to-Lymphocyte Ratio with the Risk of Thromboembolism and Mortality in Patients with Cancer - Grilz, Ella; Posch, Florian; Königsbrügge, Oliver; Schwarzinger, Ilse; Lang, Irene Marthe; Marosi, Christine; Pabinger, Ingrid; Ay, Cihan (Thrombosis and Haemostasis, 2018)
Patients with cancer are at risk of developing venous and arterial thromboembolism (VTE and ATE). Elevated platelet-to-lymphocyte (PLR) and neutrophil-to-lymphocyte ratios (NLR) have been suggested as potential biomarkers for cancer-associated chronic inflammation, VTE and mortality. We investigated the association between PLR and NLR with VTE, ATE and mortality in patients with cancer. Within a prospective cohort study, we followed-up patients with newly diagnosed or progressing cancer for objectively confirmed, symptomatic VTE, ATE and death. Fine and Gray competing-risk regression was used to model the risk of VTE and ATE. Overall survival was analysed with Kaplan–Meier estimators. From 2003 to 2013, 1,469 patients with solid cancer (median age: 61 years; 47.3% female) were recruited and followed for 2 years. Overall, 128 (8.7%) patients developed VTE, 41 (2.8%) ATE and 643 (43.8%) patients died. The sub-distribution hazard ratios (SHRs) for VTE per doubling of PLR and NLR were 1.0 (95% confidence interval [CI]: 0.8–1.3, p = 0.899) and 1.2 (1.0–1.4, p = 0.059), respectively. For ATE, the SHR per doubling of PLR and NLR were 1.0 (0.7–1.5, p = 0.940) and 1.2 (0.9–1.6, p = 0.191), respectively. A higher PLR (hazard ratio [HR] per doubling = 1.5, 1.4–1.7, p < 0.001) and a higher NLR (HR per doubling = 1.5, 1.4–1.7, p < 0.001) were associated with an increased risk of mortality after adjusting for age, sex and cancer stage. There was no statistically significant association between NLR and VTE occurrence in patients with cancer. Neither PLR nor NLR were associated with the risk of ATE. Both elevated PLR and NLR were independently associated with a twofold increased risk of mortality.
Keywords: thrombosis; cancer; platelet-to-lymphocyte ratio; neutrophil-to- lymphocyte ratio